2014
DOI: 10.1111/sji.12208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immune Response Elicited by Inulin as an Adjuvant with Filarial Antigens in Mice Model

Abstract: Filariasis caused by infectious parasitic nematodes has been identified as the second leading source of permanent and long-term disability in Sub-Saharan Africa, Asia and Latin America. Several vaccine candidates were identified from infective third-stage larvae (L3) which involves in the critical transition from arthropod to human. Hitherto studies of these antigens in combination with alum adjuvant have shown to elicit its characteristic Th2 responses. Inulin is a safe, non-toxic adjuvant that principally st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Immunizing mice with inulin as the adjuvant with other filarial antigens derived from B . malayi , demonstrated that the adjuvant induced a balanced Th1/Th2 response [ 75 ]. In the present study, a limited Th2 cytokine response and positive IgG1 titers was seen in mice immunized with Ov- 103 and Advax 1 or CpG, yet parasite killing was absent.…”
Section: Discussionmentioning
confidence: 99%
“…Immunizing mice with inulin as the adjuvant with other filarial antigens derived from B . malayi , demonstrated that the adjuvant induced a balanced Th1/Th2 response [ 75 ]. In the present study, a limited Th2 cytokine response and positive IgG1 titers was seen in mice immunized with Ov- 103 and Advax 1 or CpG, yet parasite killing was absent.…”
Section: Discussionmentioning
confidence: 99%
“…Many filarial proteins including secreted larval acidic protein 1 from Onchocerca volvulus, an ALT-2 homologue, have been characterized [47]. A chimeric protein construct comprising thioredoxin, transglutaminase and abundant larval transcript-2 (ALT-2) showed enhanced immunological response [48].…”
Section: Immuno-reactivity With Human Clinical Seramentioning
confidence: 99%
“…Earlier studies showed that protective antibodies can kill filarial parasites by ADCC-mediated mechanism (Chandrashekar et al, 1990; Mahalakshmi et al, 2014). In the in vitro cytotoxicity assay, anti-P-TUFT-ALT-2 and anti-E-ALT-2 sera illustrated higher cytotoxicity as a number of PECs adhered to the straight and dead B. malayi L3 larvae.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro ADCC assay was performed against B. malayi L3 larvae by sera of mice immunized with recombinant antigen as described previously (Chandrashekar et al, 1990; Mahalakshmi et al, 2014). Pre-immune sera samples were used as negative control.…”
Section: Methodsmentioning
confidence: 99%